Prevalence and Risk Factors and Efforts to Reduce Dengue Fever and Dengue Hemorrhagic Fever Infections at PKU Muhammadiyah Gamping Hospital, Yogyakarta - Kusbaryanto Kusbaryanto; Abdurrasyid bin Abdurrahman; Ekorini Listiowati; Yusuf Alam Romadhon; Aisyah Rosyida (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
The incidence of Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) has increased sharply in recent decades, making these infections endemic in several parts of the world. The purpose of this study was to analyze the prevalence, risk factors, and efforts to reduce DF and DHF infections at PKU Muhammadiyah Gamping Hospital, Yogyakarta. This study employed an observational cross-sectional design. The study sample consisted of patients diagnosed with DF or DHF at general hospitals in Yogyakarta between January 2019 and December 2023 who met the inclusion and exclusion criteria. Patients with a DF or DHF diagnosis but incomplete data were excluded. Sampling was conducted using a consecutive sampling method, retrieving information from patient data recorded in medical records. The research obtained ethical approval from the PKU Muhammadiyah Gamping Hospital Ethics Committee under permit number 054/KEP-PKU/II/2024. A p-value of 0.005 indicates a correlation between the incidence of DF DHF and liver illness. The value of OR is 4.660. A p-value of 0.006 indicates a correlation between the occurrence of DF DHF and corticosteroid therapy. This study found that the incidence of Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) was correlated with diabetes, hypertension, kidney disease, and asthma/chronic lung disease, which were protective factors. However, liver disease and a history of corticosteroid therapy were identified as significant risk factors. These findings suggest that impaired liver function and long-term corticosteroid use may impair the immune response, increasing susceptibility to dengue infection and its severe manifestations. Therefore, clinical management and prevention strategies should prioritize monitoring of patients with liver impairment or those undergoing corticosteroid therapy, especially in dengue-endemic areas.